2018
DOI: 10.1007/s40094-018-0296-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion trapping behavior of TiO2 nanoparticles on different parameters of weakly polar nematic liquid crystal

Abstract: In the present investigation, TiO 2 -doped weakly polar nematic liquid crystal (NLC) has been studied. This study mainly focuses on dielectric, electro-optical and optical properties of pure NLC and doped systems. Variation in different parameters like dielectric permittivity, dielectric loss, dielectric anisotropy and conductivity has been noticed. Permittivity of the doped system is almost the same as undoped system. With doping concentration, the ionic contribution to the dielectric loss as observed in low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…The result indicates that the orientational order of the LC is improved when the ionic impurities are greatly suppressed. This result is consistent with a recent report in the literature [64] that showed that the ion-trapping effect by TiO 2 nanoparticles in an LC enhances its ∆ε by improving the orientation order of LC molecules.…”
Section: Enhanced Dielectric Anisotropy In the H-bn/ito Cellsupporting
confidence: 93%
See 1 more Smart Citation
“…The result indicates that the orientational order of the LC is improved when the ionic impurities are greatly suppressed. This result is consistent with a recent report in the literature [64] that showed that the ion-trapping effect by TiO 2 nanoparticles in an LC enhances its ∆ε by improving the orientation order of LC molecules.…”
Section: Enhanced Dielectric Anisotropy In the H-bn/ito Cellsupporting
confidence: 93%
“…Free ions are also foreign charged particles and exist as impurities in the LC. The reduction of free ion impurities results in an increase in the scalar order parameter by enhancing the intermolecular association in the nematic phase [64]. The dielectric anisotropy in the nematic phase is defined as ∆ε = ε − ε ⊥ , where ε | | and ε ⊥ are the dielectric components parallel and perpendicular ton, respectively.…”
Section: Enhanced Dielectric Anisotropy In the H-bn/ito Cellmentioning
confidence: 99%
“…Допирование ЖК наночастицами (НЧ) является важной стратегией для управления их свойствами, поскольку полученные нанокомпозиты (НК) могут демонстрировать значительно отличающиеся и улучшенные характеристики в сравнении с чистыми ЖК-аналогами [13][14][15][16][17][18]. Известно, что внедрение НЧ в ЖК-матрицу приводит к снижению порогового напряжения и уменьшению времени отклика электрооптических устройств без существенного влияния на их прозрачность [19][20][21][22][23].…”
Section: ≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡...unclassified
“…In addition to the problem of the lowered transmittance, the electro-optical properties of the device may be lowered due to the free ions generated by impurities during the synthesis of the LC [ 17 , 18 ]. These free ions move between the electrodes and induce a screening effect, thereby degrading the performance of the device [ 19 ].…”
Section: Introductionmentioning
confidence: 99%